2012
DOI: 10.2169/internalmedicine.51.7590
|View full text |Cite
|
Sign up to set email alerts
|

Acute Combined Central and Peripheral Demyelination Showing Anti-Aquaporin 4 Antibody Positivity

Abstract: Neuromyelitis optica spectrum disorder (NMOSD) is characterized by optic neuritis or transverse myelitis with anti-aquaporin 4 (AQP4) antibodies (1). We herein present the case of a patient with NMOSD who also was affected with peripheral neuropathy. A 58-year-old woman developed gait disturbance and sensory impairment in the lower limbs. She exhibited longitudinally extensive transverse myelitis with anti-AQP4 antibodies. Nerve conduction studies showed demyelinating changes. Laboratory findings showed hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Kitada et al . reported an HCV-infected patient with simultaneous central and peripheral demyelination in association with anti-AQP4 antibodies and negative systemic autoimmune markers [ 8 ]. The clinical picture improved after sequential treatment with high-dose intravenous steroid and plasma exchange.…”
Section: Neuromyelitis Opticamentioning
confidence: 99%
See 1 more Smart Citation
“…Kitada et al . reported an HCV-infected patient with simultaneous central and peripheral demyelination in association with anti-AQP4 antibodies and negative systemic autoimmune markers [ 8 ]. The clinical picture improved after sequential treatment with high-dose intravenous steroid and plasma exchange.…”
Section: Neuromyelitis Opticamentioning
confidence: 99%
“…We here review known demyelinating disorders of the central nervous system (CNS) and of the peripheral nervous system (PNS) occurring in association with chronic HCV-infection. We also describe a case of HCV-related neuromyelitis optica (NMO) with circulating anti-aquaporin-4-IgG, an association previously reported in a single patient [ 8 ]. Finally, we call attention to the significantly increased prevalence of demyelinating neuropathy with monoclonal IgM anti-myelin-associated glycoprotein (MAG) antibodies, accounting for 5%, in a consecutive case series of 59 HCV-infected patients, as opposed to the estimated frequency of 0.001-0.005% in the adult population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromyelitis optica (NMO) is another inflammatory demyelinating disease of the CNS which is characterized by lesions confined to the optic nerve and spinal cord, especially longitudinally extensive spinal cord lesions [ 4 ], antiaquaporin-4 (AQP-4) autoantibody seropositivity [ 5 ], and astrocytic impairment associated with the loss of AQP-4 in NMO lesions [ 6 ]. There have been limited reports about the characteristics of peripheral neuropathy as a complication of NMO [ 7 , 8 ]. In this paper, we evaluated the electrophysiological changes with nerve conduction studies (NCS) in MS and NMO patients and showed the characteristics and differences between peripheral neuropathy as a complication of MS and NMO.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, NCS revealed abnormalities of various types and degree in approximately half of the neurologically asymptomatic patients with hepatitis C. Twenty percent of the patients had PN, 23.3% CTS, and 6.6% PN associated with CTS. In the relevant literature, symmetric sensorimotor PN of mostly the axonal type and mononeuropathy multiplex are reported in association with hepatitis C infection (22). However, in patients lacking cryoglobulin, demyelinating PN dominate (23,24).…”
Section: Discussionmentioning
confidence: 99%